Fire Extinguisher System Hard Skill Improvement Training at the Inalum Building, Batubara Regency (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
A fire alarm is an early warning system for the danger of Fire. If early warning of the danger of Fire is active, officers immediately look for fire spots to extinguish. If the Fire is still small or medium, the Fire can be extinguished with a light fire extinguisher. If the Fire is big, it is extinguished with a sprinkler or water from the hydrant system. The Inalum building only started operating in 2021, and the workers in building management have yet to experience fire extinguisher systems. For this reason, it is necessary to carry out hard skills training regarding fire extinguisher systems. The aim is for workers to understand how the fire extinguisher works and that the building is ready to face the dangers of Fire. The training results showed that the workers' hard skills increased by 21.03%, initially only 74.48% before and increased to 95.51% after the training. This learning process was considered satisfactory by the training participants. The benefits of the training received a score of 4.89 on a scale of 5 by the participants.